Morphological variation in herring (Clupea harengus membras) : spring and autumn spawners in the Bothnian Sea - Blass, Martina (SLU/Dept. Of Aquatic Resources, 2014)
There are two spawning types of herring (Clupea Harengus m.) in the Bothnian sea. The aim of this thesis was to investigate if there are morphological differences between the spring and autumn spawners, and also study whether freezing affect the morphological measurements of herring. This was done by landmark based morphometrics. 150 herring were collected from the Forsmark area in the Bothnian Sea to investigate the effects of freezing. 316 specimens were caught in the area of Gävle and Hudiksvall, during spring and autumn in 2012. The results showed that freezing does affect morphological measurements mainly by shrinking the measurements connected to body length. Once herrings had been frozen, there were very little changes in morphology. The morphometric study of spawners confirms the claims by local fishermen, that there is a morphological difference between spring and autumn spawning herring. The spring spawners had a rela-tively larger eye, deeper head and thicker caudal peduncle, whereas autumn spawners overall had a relatively more elongated body shape. This study confirms recent genetic studies (Barrio et al. submitted for publication) that the two spawning groups are different populations and might need different management plans. The method used in this study presents a cost-effective way of determining parts of the different populations in a mixed fishery.